Effect of Trichosanthes cucumerina Methanol Extract on CRP and Fibrinogen Levels in Diabetic Ulcer Rat Models - Shafriani, Nazula Rahma; Astuti, Tri Dyah; Amri, Shofy Farha Aulia; Permana, Riski Aditya; Fridhoriansyah, Zuvi; Maharani, Intan (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Diabetic ulcers can be fatal for people with long-term diabetes. This is caused by the spread of diabetic ulcers and inadequate care for the wound, which can induce an infection and even death. This study aims to determine inflammatory markers, specifically fibrinogen and C-Reactive Protein (CRP), as indicators of healing, particularly in a rat model of diabetic ulcers treated with Trichosanthes cucumerina methanol extract. The methods used were making extracts, measuring blood glucose levels, measuring CRP, and measuring fibrinogen levels in 25 male Wistar rats. Based on the results of glucose and fibrinogen examinations in all groups before treatment and after treatment, it showed a decrease in glucose and fibrinogen levels. Meanwhile, the results of CRP examinations, before and after treatment did not show any differences. The results of statistical analysis showed that there was a significant difference of p<0.05 in pre and post glucose, as well as pre and post fibrinogen.The extract that reduced fibrinogen levels the most was group 3 with 500 mg/KgBW. Meanwhile, CRP levels before and after treatment did not show a decrease.